Development of business plans in an information-based, market-oriented economy - Hayes, Robert M. (ASLIB LondonGB)
Discusses two contexts for development of business plans in an information economy: firstly for industry in general and secondly for information industry companies. Discusses the implications, both specific to business planning and more general to societal needs, which these issues have for national policies. Looks at the context of the 'Information economy' of Yugoslavia.